(untitled) (Altre Modernità, 2021)
ABSTRACT: This article aims to study the different ways of shaping posthuman identities, which originates from archetypical metamorphoses and human-animal hybrids. This new imaginary rescues a premodern perspective about the animal, in order to dismantle the boundaries that have defined the human subject since the European modern age. In some books published in the past twenty years, the interspecies encounter outlines a new identity concept. Firstly, the article examines how the becoming-animal concept merges with the feminine subject’s emancipation, as well as with the deconstruction of the patriarchal family structure; secondly, it explores the conjunctions between human-animal hybrids and cyborgs.